Implementation of Fuzzy PID Controller in Cascade with Anti-Windup to Real-Scale Test Equipment for Pavements - REYES-ORTIZ, Oscar Javier; USECHE-CASTELBLANCO, Juan Sebastian; VARGAS-FONSECA, German Leandro (Engineering Transactions, 2020)
In the industry and academia, large-scale equipment has been developed, which requires control systems that provide safety and efficiency with the lowest possible energy consumption. In the industrial cascade control system, nested controllers have been a versatile tool for the control of large-scale equipment. Research shows that these types of controllers improve their performance with the integration of artificial intelligence algorithms and prevention methods against controller saturation. For this reason, this paper presents the development of a fuzzy proportional-integral-derivative (PID) controller in cascade with anti-windup (AW) for full-scale test equipment for pavements. In this study, the mathematical expressions for the equipment, the design of the controller and additional systems for comparison, simulation and analysis are developed. The main objective is to test the functionality of this type of nested controllers for these systems.